Answer:
multiply 18 and 13, which is equal to 234. then multiply that by $5.86 which is equal to $1371.24 then the last step add that by $800. which is equal to $2171.24. hope this helps
Answer:
6
Step-by-step explanation:
6 because 6/2=3,6/3=2
Answer:
![\frac{10}{15}-\frac{2}{5}=\frac{4}{15}](https://tex.z-dn.net/?f=%5Cfrac%7B10%7D%7B15%7D-%5Cfrac%7B2%7D%7B5%7D%3D%5Cfrac%7B4%7D%7B15%7D)
Step-by-step explanation:
We know that
- A fraction consists of two integers—one on the top, and one on the bottom.
- The top one is numerator, the bottom one is denominator, and
- These two numbers are separated by a line.
Let us consider two different fractions with different denominators
Lets subtract the two fractions
![\frac{10}{15}-\frac{2}{5}\:\:\:\:](https://tex.z-dn.net/?f=%5Cfrac%7B10%7D%7B15%7D-%5Cfrac%7B2%7D%7B5%7D%5C%3A%5C%3A%5C%3A%5C%3A)
![\mathrm{Cancel\:}\frac{10}{15}:\quad \frac{2}{3}](https://tex.z-dn.net/?f=%5Cmathrm%7BCancel%5C%3A%7D%5Cfrac%7B10%7D%7B15%7D%3A%5Cquad%20%5Cfrac%7B2%7D%7B3%7D)
![=\frac{2}{3}-\frac{2}{5}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2%7D%7B3%7D-%5Cfrac%7B2%7D%7B5%7D)
![\mathrm{Least\:Common\:Multiplier\:of\:}3,\:5:\quad 15](https://tex.z-dn.net/?f=%5Cmathrm%7BLeast%5C%3ACommon%5C%3AMultiplier%5C%3Aof%5C%3A%7D3%2C%5C%3A5%3A%5Cquad%2015)
![\mathrm{Adjust\:Fractions\:based\:on\:the\:LCM}](https://tex.z-dn.net/?f=%5Cmathrm%7BAdjust%5C%3AFractions%5C%3Abased%5C%3Aon%5C%3Athe%5C%3ALCM%7D)
![\mathrm{For}\:\frac{2}{3}:\:\mathrm{multiply\:the\:denominator\:and\:numerator\:by\:}\:5](https://tex.z-dn.net/?f=%5Cmathrm%7BFor%7D%5C%3A%5Cfrac%7B2%7D%7B3%7D%3A%5C%3A%5Cmathrm%7Bmultiply%5C%3Athe%5C%3Adenominator%5C%3Aand%5C%3Anumerator%5C%3Aby%5C%3A%7D%5C%3A5)
![\frac{2}{3}=\frac{2\cdot \:5}{3\cdot \:5}=\frac{10}{15}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D%3D%5Cfrac%7B2%5Ccdot%20%5C%3A5%7D%7B3%5Ccdot%20%5C%3A5%7D%3D%5Cfrac%7B10%7D%7B15%7D)
![\mathrm{For}\:\frac{2}{5}:\:\mathrm{multiply\:the\:denominator\:and\:numerator\:by\:}\:3](https://tex.z-dn.net/?f=%5Cmathrm%7BFor%7D%5C%3A%5Cfrac%7B2%7D%7B5%7D%3A%5C%3A%5Cmathrm%7Bmultiply%5C%3Athe%5C%3Adenominator%5C%3Aand%5C%3Anumerator%5C%3Aby%5C%3A%7D%5C%3A3)
![\frac{2}{5}=\frac{2\cdot \:3}{5\cdot \:3}=\frac{6}{15}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B5%7D%3D%5Cfrac%7B2%5Ccdot%20%5C%3A3%7D%7B5%5Ccdot%20%5C%3A3%7D%3D%5Cfrac%7B6%7D%7B15%7D)
so
![=\frac{10}{15}-\frac{6}{15}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B10%7D%7B15%7D-%5Cfrac%7B6%7D%7B15%7D)
![\mathrm{Since\:the\:denominators\:are\:equal,\:combine\:the\:fractions}:\quad \frac{a}{c}\pm \frac{b}{c}=\frac{a\pm \:b}{c}](https://tex.z-dn.net/?f=%5Cmathrm%7BSince%5C%3Athe%5C%3Adenominators%5C%3Aare%5C%3Aequal%2C%5C%3Acombine%5C%3Athe%5C%3Afractions%7D%3A%5Cquad%20%5Cfrac%7Ba%7D%7Bc%7D%5Cpm%20%5Cfrac%7Bb%7D%7Bc%7D%3D%5Cfrac%7Ba%5Cpm%20%5C%3Ab%7D%7Bc%7D)
![=\frac{10-6}{15}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B10-6%7D%7B15%7D)
![\mathrm{Subtract\:the\:numbers:}\:10-6=4](https://tex.z-dn.net/?f=%5Cmathrm%7BSubtract%5C%3Athe%5C%3Anumbers%3A%7D%5C%3A10-6%3D4)
![=\frac{4}{15}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B4%7D%7B15%7D)
Therefore,
![\frac{10}{15}-\frac{2}{5}=\frac{4}{15}](https://tex.z-dn.net/?f=%5Cfrac%7B10%7D%7B15%7D-%5Cfrac%7B2%7D%7B5%7D%3D%5Cfrac%7B4%7D%7B15%7D)
The equation of line perpendicular to given line is:
![y = \frac{2}{3}x-1](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B2%7D%7B3%7Dx-1)
Step-by-step explanation:
Given equation is:
![3x+2y = -8](https://tex.z-dn.net/?f=3x%2B2y%20%3D%20-8)
First of all, we have to find the slope of the given line
So,
![3x+2y = -8\\2y = -3x-8\\](https://tex.z-dn.net/?f=3x%2B2y%20%3D%20-8%5C%5C2y%20%3D%20-3x-8%5C%5C)
Dividing both sides by 2
![\frac{2y}{2} = \frac{-3x-8}{2}\\y = \frac{-3x}{2} - \frac{8}{2}\\y =-\frac{3}{2}x-4](https://tex.z-dn.net/?f=%5Cfrac%7B2y%7D%7B2%7D%20%3D%20%5Cfrac%7B-3x-8%7D%7B2%7D%5C%5Cy%20%3D%20%5Cfrac%7B-3x%7D%7B2%7D%20-%20%5Cfrac%7B8%7D%7B2%7D%5C%5Cy%20%20%3D-%5Cfrac%7B3%7D%7B2%7Dx-4)
As the equation is in slope-intercept form, the co-efficient of x will be the slope of the line
![m_1 = -\frac{3}{2}](https://tex.z-dn.net/?f=m_1%20%3D%20-%5Cfrac%7B3%7D%7B2%7D)
As we know that product of slopes of two perpendicular lines is -1
Let m-2 be the slope of line perpendicular to given line
![m_1.m_2 = -1\\-\frac{3}{2} . m_2 = -1\\m_2 = -1 * -\frac{2}{3}\\m_2 = \frac{2}{3}](https://tex.z-dn.net/?f=m_1.m_2%20%3D%20-1%5C%5C-%5Cfrac%7B3%7D%7B2%7D%20.%20m_2%20%3D%20-1%5C%5Cm_2%20%3D%20-1%20%2A%20-%5Cfrac%7B2%7D%7B3%7D%5C%5Cm_2%20%3D%20%5Cfrac%7B2%7D%7B3%7D)
Slope-intercept form is:
![y = m_2x+b](https://tex.z-dn.net/?f=y%20%3D%20m_2x%2Bb)
putting the value of the slope
![y = \frac{2}{3}x+b](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B2%7D%7B3%7Dx%2Bb)
Putting the point (3,1) in the equation
![1 = \frac{2}{3}(3) +b\\1 = 2 + b\\b = 1-2\\b = -1](https://tex.z-dn.net/?f=1%20%3D%20%5Cfrac%7B2%7D%7B3%7D%283%29%20%2Bb%5C%5C1%20%3D%202%20%2B%20b%5C%5Cb%20%3D%201-2%5C%5Cb%20%3D%20-1)
Putting the value of b
![y = \frac{2}{3}x-1](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B2%7D%7B3%7Dx-1)
Hence,
The equation of line perpendicular to given line is:
![y = \frac{2}{3}x-1](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B2%7D%7B3%7Dx-1)
Keywords: Slope-intercept form, slope
Learn more about equation of line at:
#LearnwithBrainly
Answer:
X could be 2, 3, 4, 5, 6, 7, 8, or 9.
So, your final answer could be either 52, 53, 54, 55, 56, 57, 58, or 59.